Compatibility of the gH homologs of Epstein-Barr virus and related lymphocryptoviruses - Wu, Liguo (2007)
Glycoprotein gH, together with its chaperone gL and a third glycoprotein gB, is essential to cell cell fusion and virus cell fusion mediated by herpesviruses. Epstein-Barr virus (EBV), the prototype human lymphocryptovirus, requires a fourth glycoprotein gp42 to support fusion with B cells in addition to epithelial cells. Two other lymphocryptoviruses, the rhesus lymphocryptovirus (Rh-LCV) and the common marmoset lymphocryptovirus (CalHV3), have been sequenced in their entirety and each has a gp42 homolog. Combinations of proteins from EBV, Rh-LCV and CalHV3 were able to mediate fusion of epithelial cells, but, even when complexed with EBV gp42, only RhLCV and not CalHV3 proteins were able to mediate fusion with human B cells. CalHV3 gL was also unable to function effectively as a chaperone for EBV or Rh-LCV gH. The Rh-LCV gH homolog supported more fusion than EBV gH with an epithelial cell and supported the highest levels of fusion with a B cell. Chimeric constructs made from Rh-LCV gH and EBV gH which have 85.4% sequence identity should prove useful for mapping the regions of gH that are of importance to fusion as a whole and to B cell fusion in particular.